Tutor-student interaction in undergraduate chemistry: a case of learning to make relevant distinctions of molecular structures for determining oxidation states of atoms. Issue 16 (2nd November 2018) - Manneh, Ilana A.; Rundgren, Carl-Johan; Hamza, Karim M.; Eriksson, Lars
ABSTRACT: In this study, we explore the issues and challenges involved in supporting students' learning to discern relevant and critical aspects of determining oxidation states of atoms in complex molecules. We present a detailed case of an interaction between three students and a tutor during a problem-solving class, using the analytical tool of practical epistemology analysis (PEA). The results show that the ability to make relevant distinctions between the different parts of a molecule for solving the problem, even with the guidance of the tutor, seemed to be challenging for students. These shifts were connected to both purposes that were specific for solving the problem at hand, and additional purposes for general learning of the subject matter, in this case how to assign oxidation states in molecules. The students sometimes could not follow the additional purposes introduced by the tutor, which made the related distinctions more confusing. Our results indicate that in order to provide adequate support and guidance for students the tutor needs to consider how to sequence, move between, and productively connect the different purposes introduced in a tutor-student interaction. One way of doing that is by first pursuing the purposes for solving the problem and then successively introduce additional, more general purposes for developing students' learning of the subject matter studied. Further recommendations drawn from this study are discussed as well.